2020
DOI: 10.2147/ppa.s265126
|View full text |Cite
|
Sign up to set email alerts
|

<p>Patient-Reported Outcomes and Impact of Type 2 Diabetes: A Cross-Sectional Study in the Kingdom of Saudi Arabia</p>

Abstract: Background The Kingdom of Saudi Arabia (KSA) has the second highest prevalence of type 2 diabetes mellitus (T2DM) in the Middle East. There is a paucity of research on the experiences and treatment preferences of patients with T2DM in KSA. This study explored Saudi patients’ health-related quality of life, eating habits, experiences during Ramadan, and preference between two glucagon-like peptide-1 receptor agonist (GLP-1 RA) treatment devices. Methods A cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
(40 reference statements)
1
9
0
1
Order By: Relevance
“…The most studied condition was diabetes mellitus (n=4), [23][24][25][26] followed by musculoskeletal disorders, back pain, and injuries (n=3). [27][28][29] The remaining articles focused either on a specific condition, such as urinary…”
Section: Comparison Of Results By Condition or Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The most studied condition was diabetes mellitus (n=4), [23][24][25][26] followed by musculoskeletal disorders, back pain, and injuries (n=3). [27][28][29] The remaining articles focused either on a specific condition, such as urinary…”
Section: Comparison Of Results By Condition or Treatmentmentioning
confidence: 99%
“…35 The sample size of each study was related to the condition of interest. Out of a summed sample equal to 2025 patients, 36% had diabetes, [23][24][25][26] -unsurprising considering that the prevalence of diabetes in the KSA exceeds 14% of the population. 36 The second largest sample study was patients who had cardiovascular diseases, which also affect millions in the KSA.…”
Section: Dovepressmentioning
confidence: 99%
“…Differences between men and women in knowledge, attitude, and practice may explain part of these results during Ramadan. It has been shown that more women than men broke the fast in relation to diabetes concerns (81,82). Additionally, women changed their medications during Ramadan (81) and have lower drug adherence than men, especially for high-cost drugs (83).…”
Section: Discussionmentioning
confidence: 99%
“…The Kingdom of Saudi Arabia (KSA), part of the Eastern Mediterranean region (EMR), is one of the fastest growing economies in the world. The escalation in household income in the beginning of the 21st century was accompanied with a fast nutrition transition and an increased consumption of SSF, associated with a heavy burden of obesity, food allergies, and NCD [ 8 , 9 , 10 , 11 ]. Recent data by the World Health Organization (WHO) and the Global Burden of Disease (GBD) revealed that KSA is among the top countries in the region and the world in the prevalence of obesity and diabetes.…”
Section: Introductionmentioning
confidence: 99%